International Relations in the Far East and Russia in the Late 19th and Early 20th Centuries - Omonov Abror Qurbonovich (Indonesian Journal of Innovation Studies, 2019)
After the "Madzi Revolution" of 1868, capitalism in Japan grew at a particularly high rate. Japan also felt the need for colonization. Therefore, Japan took active steps, first and foremost, to Korea and Manjuria. Japanese Foreign Minister Marx Ito announced that if China's interests in Korea are only historically important, Japan's interests will be linked to economic needs.